Salvia miltiorrhiza and Its Compounds as Complementary Therapy for Dyslipidemia: A Meta-Analysis of Clinical Efficacy and In Silico Mechanistic Insights - Min-Seong Lee; Han-Young Lee; Seung-Hyun Oh; Chang-Bum Kim; Ji-Han Kim; Seung-Hoon Yoo; Yeon-Joo Yoo; Su-Yeon Lee; Byung-Cheol Lee (MDPI AG, 2024)
Background/Objectives: Dyslipidemia is a significant risk factor for atherosclerotic cardiovascular disease (ASCVD), a leading cause of death worldwide. Salvia miltiorrhiza Burge is widely used in East Asia for cardiovascular health, showing potential benefits in lowering cholesterol and reducing inflammation. Methods: This study systematically reviewed and conducted a meta-analysis of randomized controlled trials (RCTs) to assess the clinical effectiveness of Salvia miltiorrhiza in treating dyslipidemia. Moreover, network pharmacology and molecular docking analyses were performed to explore the mechanisms underlying the effects of Salvia miltiorrhiza. Results: The meta-analysis revealed that when Salvia miltiorrhiza is combined with statin therapy, it significantly enhances lipid profiles, including reductions in total cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglycerides and improvements in high-density lipoprotein cholesterol (HDL-C), compared to statin therapy alone. The in silico analyses indicated that Salvia miltiorrhiza may influence key biological pathways, such as the PI3K/Akt, JAK/STAT, and HMGCR pathways, which are involved in inflammation, lipid metabolism, and the development of atherosclerosis. Conclusions: Salvia miltiorrhiza shows potential as a complementary therapy for dyslipidemia, offering additional lipid-lowering and anti-inflammatory benefits.